Routine educational outcome measures in health studies: Key Stage 1 in the ORACLE Children Study follow-up of randomised trial cohorts. Issue 1 (7th October 2010) - Jones, David R; Pike, Katie; Kenyon, Sara; Pike, Laura; Henderson, Brian; Brocklehurst, Peter; Marlow, Neil; Salt, Alison; Taylor, David J
Abstract : Objectives: Statutory educational attainment measures are rarely used as health study outcomes, but Key Stage 1 (KS1) data formed secondary outcomes in the long-term follow-up to age 7 years of the ORACLE II trial of antibiotic use in preterm babies. This paper describes the approach, compares different approaches to analysis of the KS1 data and compares use of summary KS1 (level) data with use of individual question scores. Participants: 3394 children born to women in the ORACLE Children Study and resident in England at age 7. Methods: Analysis of educational achievement measured by national end of KS1 data (KS1) using Poisson regression modelling and anchoring of the KS1 data using external standards. Results: KS1 summary level data were obtained for 3239 (95%) eligible children; raw individual question scores were obtained for 1899 (54%). Use of individual question scores where available did not change the conclusion of no evidence of treatment effects based on summary KS1 outcome data. Conclusions: When accessible for medical research purposes, routinely collected educational outcome data may have advantages of low cost and standardised definition. Here, summary scores lead to similar conclusions to raw (individual question) scores and so are attractive and cost-effective alternatives.